2014
DOI: 10.15252/emmm.201404436
|View full text |Cite
|
Sign up to set email alerts
|

N‐WASP is required for Amphiphysin‐2/BIN1‐dependent nuclear positioning and triad organization in skeletal muscle and is involved in the pathophysiology of centronuclear myopathy

Abstract: Mutations in amphiphysin-2/BIN1, dynamin 2, and myotubularin are associated with centronuclear myopathy (CNM), a muscle disorder characterized by myofibers with atypical central nuclear positioning and abnormal triads. Mis-splicing of amphiphysin-2/BIN1 is also associated with myotonic dystrophy that shares histopathological hallmarks with CNM. How amphiphysin-2 orchestrates nuclear positioning and triad organization and how CNM-associated mutations lead to muscle dysfunction remains elusive. We find that N-WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(140 citation statements)
references
References 67 publications
4
134
0
2
Order By: Relevance
“…Previous work, based on overexpression of the KASH domain to displace endogenous nesprins, suggested that nesprins are not necessary for distributing nuclei in myotubes (Falcone et al, 2014;Metzger et al, 2012). In our system, siRNA-mediated depletion of nesprins reported here had a more substantial impact on nuclear distribution (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…Previous work, based on overexpression of the KASH domain to displace endogenous nesprins, suggested that nesprins are not necessary for distributing nuclei in myotubes (Falcone et al, 2014;Metzger et al, 2012). In our system, siRNA-mediated depletion of nesprins reported here had a more substantial impact on nuclear distribution (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…The fourth nuclear migration event in developing myotubes is towards the periphery of the syncytium, similar to how nuclei move in myofibers that recover from injury (Falcone et al, 2014;Romero, 2010) (Fig. 2D).…”
Section: Nuclear Movements and Muscle Developmentmentioning
confidence: 62%
“…2D). This nuclear movement is dependent on the correct spreading of the nuclei in the previous step, as well as a complex formed between the F-BAR protein amphiphysin-2 and the actinnucleator neuronal Wiskott-Aldrich Syndrome protein (N-WASP) (Falcone et al, 2014). Furthermore, amphiphysin-2 is recruited to the surface of nuclei through an interaction with nesprin-2 (D' Alessandro et al, 2015).…”
Section: Nuclear Movements and Muscle Developmentmentioning
confidence: 99%
“…Les réseaux de cytosquelette d'actine et de microtubules sont totalement remodelés durant la maturation des fibres musculaires avec une forte accumulation péri-nucléaire observée en comparaison à leur organisation dans des cellules mononuclées. Récemment, ces réseaux cytosquelettiques ont été mis en évidence comme un potentiel support à la « périphé-risation » des noyaux [5]. Les conséquences fonctionnelles d'une mauvaise localisation des noyaux sur les fibres ont longtemps suscité des interrogations.…”
Section: Identification De Nouveaux Régulateurs Du Positionnement Nucunclassified
“…stratégie d'identification protéomique différentielle entre des fibres musculaires immatures et matures grâce à une méthode originale de culture in vitro de cellules primaires de souris ( Figure 1A) [5]. Cette analyse nous a permis d'identifier et de sélectionner un premier groupe de protéines (249) (Figure 1B).…”
Section: Les Auteurs Déclarent N'avoir Aucun Lien D'intérêt Concernanunclassified